REKONSTRUKSI PENDIDIKAN DI SEKOLAH DASAR DALAM PERSPEKTIF FILSAFAT ILMU: MEMBANGUN KARAKTER DAN MENGEMBANGKAN POTENSI INDIVIDU SECARA HOLISTIK - Bisma Nurillah Manahim; Budi Purwoko; Lamijan Hadi Susarno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to reconstruct elementary education from the perspective of philosophy of science, focusing on how education can play a role in building character and developing individuals holistically. The research uses a qualitative approach with a literature study methodology, analyzing theories of character education, constructivist learning, and multiple intelligences in elementary education. The findings reveal that most elementary schools still emphasize academic achievement (IQ), often neglecting the social, emotional, and kinesthetic development of students. Although efforts to integrate character education are made, they remain limited and are often treated as extracurricular activities rather than being embedded in the daily learning process. The study suggests a shift towards a more holistic educational approach, one that integrates cognitive, social, emotional, and moral aspects to foster well-rounded individuals who are not only academically capable but also socially responsible and emotionally intelligent. The research contributes to the understanding of holistic education and proposes recommendations for improving the integration of character education in elementary schools.